Railway noise in a residential area : a case study. - Chan, Jia Wei; Sulaiman, Wan Nor Azmin; Abu Samah, Mohd. Armi (ICFAI University Press, 2009)
The increasing number of urban railway lines laid around residential areas has inevitably caused major noise pollution problems to the residents. Noise pollution can cause health problems. The objectives of the study were to assess the level of railway noise, to research the existing attitudes and response of residents on railway noise in a selected sampling area and to compare noise levels during different time interval in Serdang Lama. The noise parameters measured were LAeq, Lmax, Lmin, L10, L50 and L90. Data and statistical analyses were done on the data samples. The study revealed that, on a daily basis, the noise level exposure experienced by the residents exceeded the limits set by World Health Organization.